Isolation of a Lactobacillus paracasei Strain with Probiotic Attributes from Kefir Grains - Stavros Plessas (Biomedicines, 2020)
Κefir is a rich source of potentially probiotic bacteria. In the present study, firstly, in vitro screening for probiotic characteristics of ten lactic acid bacteria (LAB) isolated from kefir grains was performed. Strain AGR 4 was selected for further studies. Molecular characterization of strain AGR 4, confirmed that AGR 4 belongs to the Lactobacillus paracasei (reclassified to Lacticaseibacillus paracasei subsp. paracasei) species. Further testing revealed that L. paracasei AGR 4 displayed adhesion capacity on human adenocarcinoma cells, HT-29, similar to that of the reference strain, L. casei ATCC 393. In addition, the novel strain exerted significant time- and dose-dependent antiproliferative activity against HT-29 cells and human melanoma cell line, A375, as demonstrated by the sulforhodamine B cytotoxicity assay. Flow cytometry analysis was employed to investigate the mechanism of cellular death; however, it was found that AGR 4 did not act by inducing cell cycle arrest and/or apoptotic cell death. Taken together, these findings promote the probiotic character of the newly isolated strain L. paracasei AGR 4, while further studies are needed for the detailed description of its biological properties.